Information content and informativeness of analysts’ report: evidence from Malaysia - Mohd Thas Thaker, Hassanudin *; Mohamad, A.; Mustaffa Kamil, N. K.; Duasa, J. (Emerald, 2018)
Purpose: This study aims to document the influence of information content and the informativeness of analyst reports towards cumulative abnormal return in the Malaysian market. Design/methodology/approach: Samples of analyst reports for the period 4th January 2010 until 24th December 2015 were collected from the Bursa Malaysia’s repository system for daily basis information. The study uses market-adjusted method for the calculation of cumulative abnormal return and panel regression to test the research objective. In addition, diagnostic tests, which include the variance inflation factor (VIF), correlation analysis, heteroscedasticity tests, serial auto-correlation and the Hausman test, were also performed to ensure the validity and reliability of the data. Findings: Result from the unbalanced panel data reveals that not all information contained in the analyst reports is able to detect stock returns movement. Only five variables are shown to have a strong association with the returns, and these are target price, earnings forecast, return on equity, cash flows to price and sales to price ratio. The R-square value has also been shown to be relatively low (0.79 per cent), indicating the low predictive power of information content and the informativeness of the analyst report in explaining stock returns. To support the findings based on the knowledge obtained, a descriptive analysis on whether the analyst reports were able to predict the recommendation accurately was performed. Result from the descriptive analysis shows that only 57 per cent of the recommendations are accurate, evidenced by the differing target price and ending price. This outcome appears to contradict the theory of signalling hypothesis. Hence, it can be concluded that analyst reports have less informational role among investors. Originality/value: This paper has, thus, provided insight into how information disclosed in the analyst report influence the return of stocks, further extending the limited research on analyst report in the context of the Malaysian markets. The paper has also added to the existing literature by providing several implications to practitioners and researchers alike.